2011
DOI: 10.1093/bja/aeq402
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative levosimendan infusion in combined aortic valve and coronary bypass surgery

Abstract: Levosimendan improved haemodynamics compared with a placebo in patients undergoing high-risk cardiac surgery. The concentrations of levosimendan's metabolites were higher compared with earlier studies using perioperative dosing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(30 citation statements)
references
References 27 publications
1
27
0
2
Order By: Relevance
“…Further filtering led to 60 articles scanned during the abstract review. From the 27 full‐text articles reviewed, 14 studies were finally included for systematic review and meta‐analysis . Figure depicts the flow diagram for the search process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further filtering led to 60 articles scanned during the abstract review. From the 27 full‐text articles reviewed, 14 studies were finally included for systematic review and meta‐analysis . Figure depicts the flow diagram for the search process.…”
Section: Resultsmentioning
confidence: 99%
“…From the 27 full-text articles reviewed, 14 studies were finally included for systematic review and meta-analysis. [8][9][10][11][12][13][14][15][16][17][18][19][20][21] Figure 1 depicts the flow diagram for the search process. Tables 1 and 2 present an overview and quality review of the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…Optimizing cardiac function could be a good strategy to minimize the risk of postoperative AKI, according to Leppikangas et al [27] . They reported that the use of preoperative calcium sensitizer infusion could be a good strategy to improve left ventricular EF in patients with high-risk cardiac surgery [27] .…”
Section: Discussionmentioning
confidence: 99%
“…They reported that the use of preoperative calcium sensitizer infusion could be a good strategy to improve left ventricular EF in patients with high-risk cardiac surgery [27] .…”
Section: Discussionmentioning
confidence: 99%
“…Myocardial dysfunction may reduce exercise tolerance and limit early postoperative physical activity. Whereas postoperative myocardial function at rest has been extensively investigated (Ng et al, 2005;Apostolakis et al, 2009;Leppikangas et al, 2011;Juhl-Olsen et al, 2012;Hashemi et al, 2013), less is known about myocardial function during physical activity in the early postoperative phase.…”
Section: Introductionmentioning
confidence: 99%